The Development Needs of Newly Appointed Senior School Leaders in the Western Cape South Africa: A Case Study - Nelius Jansen van Vuuren (International School for Social and Business Studies, 2017)
The essential role that senior school leaders play in school leadership teams to ensure effective strategic leadership in schools has been the subject of intense discussion for many years. Crucial to this debate is the establishment of professional learning and leadership approaches for newly appointed senior school leaders. Recommendations for policy and practice highlight the importance of appropriate, multifaceted, developmental support initiatives for newly appointed school leaders. In many countries, including South Africa, a teaching qualification and, in most cases, extensive teaching experience is the only requirement for being appointed as a senior school leader in a school. This tends to suggest that no further professional development is required for newly appointed school leaders, the problem addressed in this paper. This paper reports on the main findings of the perceived development needs of newly appointed senior school leaders in the Western Cape, South Africa, and suggests that school leaders occupy a unique and specialist role in education, which requires relevant and specific preparation to support effective leadership. The respondents of this study report a lack of contextualised training and support before and after their appointment in their new roles creating unique development needs. This paper, therefore, employs a mixed-method approach to gather data to understand the perceived needs of twenty newly appointed senior school leaders in the Western Cape, South Africa.